BIOTECHNOLOGICAL PROSPECTING FOR SCIENTIFIC ADVANCEMENTS: REGISTER, PROTECTION, AND INNOVATION SUGARCANE CULTIVARS (RECIMA21 - Revista Científica Multidisciplinar - ISSN 2675-6218, 2023)
Biotechnology has become a prominent field in sugarcane research and the sugarcane industry, with a focus on registering, protecting, and innovating sugarcane cultivars. This article provides an overview of the registration and protection processes for sugarcane cultivars, as well as the biotechnological advancements in this area. The study conducted a systematic review of articles published between 2017 and 2022. The research also analyzed the registration of cultivars in the National Registry of Cultivars. Additionally, a search for patents related to sugarcane varieties was performed. The results highlight the importance of genetic improvement and selection of sugarcane varieties, understanding the physiology and biochemistry of sugarcane, and the role of intellectual property rights in protecting and promoting innovation in the sugarcane industry. The analysis of registered cultivars and patents provides insights into the most sought-after traits and technological domains in sugarcane research. This study contributes to the advancement of scientific knowledge and the development of sustainable and productive sugarcane cultivars.